Exploring the commercial value of social networks: enhancing consumers' brand experience through Facebook pages. Issue 5 (19th August 2014) - Chen, Hsin; Papazafeiropoulou, Anastasia; Chen, Ta-Kang; Duan, Yanqing; Liu, Hsiu-Wen
Abstract : Purpose: This study aims to understand the factors which impact upon the consumers' willingness to utilise company Facebook pages and e-word-of mouth by proposing and testing a conceptual framework which is inspired by theories in marketing and information systems fields. We believe that only by applying both theories will provide a more complete understanding of the relationship between brand experience and Facebook. The research model attempts to illustrate the factors according to customers' intrinsic and extrinsic motivations and their impact on brand experience, brand Facebook page loyalty and e-word-of-mouth. Design/methodology/approach: We adopted an online survey method for data collection. The subjects we used were Facebook users. The data was collected in Taiwan over spring 2011. We then used the Structural Equation Model (SEM) to analyse the data collected. Findings: The findings suggest that users are influenced by the technical characterises of a brand Facebook page, such as ease of use and usefulness, which might be combated by attempting to reduce customer effort when accessing Facebook pages. We conclude that customer effort influenced brand experience and consequently loyalty to brand Facebook pages and e-word-of-mouth. Research limitations/implications: The limitations of this study relate to the investigation of consumer perspectives in a specific geographical context and time frame. Originality/value: The study's contributions are both theoretical and practical, as it offers new insights into brand experience attitudes in an online environment and useful insights to companies willing to market themselves on Facebook.